2017
DOI: 10.1016/j.carbon.2016.11.018
|View full text |Cite
|
Sign up to set email alerts
|

EDOT polymerization at photolithographically patterned functionalized graphene

Abstract: Graphene possesses unique features that make it attractive for nanotechnology. Functional devices often require combination of several materials with specific functions, and graphenepolymer composites are one of them. Herein, we report on the preparation of PEDOT:Graphene bilayers by in situ polymerization of EDOT on covalently functionalized graphene. The polymerization proceeds exclusively on the grafted graphene, and patterned structures with high spatial resolution down to 3 μm could have been prepared. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…A combination of several types of materials with different functionalities can be utilized to tailor new composites or devices with required functions. Graphene, graphene oxide and graphene platelets are currently utilized to improve the electrical, physical and mechanical properties of polymers [5][6][7][8][9][10]. Polymer matrices with graphene nanoplatelet (GNP) fillers are promising materials and are currently used in the automobile, defense and aerospace industries [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A combination of several types of materials with different functionalities can be utilized to tailor new composites or devices with required functions. Graphene, graphene oxide and graphene platelets are currently utilized to improve the electrical, physical and mechanical properties of polymers [5][6][7][8][9][10]. Polymer matrices with graphene nanoplatelet (GNP) fillers are promising materials and are currently used in the automobile, defense and aerospace industries [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene was prepared by a chemical vapor deposition (CVD) method on copper foil 52 . Isotopically labelled graphene layer was prepared using 13 CH 4 as a precursor 19 .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Several researchers have suggested that the diazotization of GO must be performed in organic solvents, in order to avoid the undesired side reactions of the aryl radicals with water affording phenolic compounds. [114][115][116][117]…”
Section: Diazotizationmentioning
confidence: 99%